The spectroscopic properties of Dy3+and Eu3+ co-doped Y3Al5O12 (YAG) phosphors for white LED - Xuejiao Niu (Progress in Natural Science: Materials International, 2015)
Tunable full color emissive Y2.94−xAl5O12: 0.06Dy3+, xEu3+ (YAG: 0.06Dy, xEu) phosphors with emission peaks at 483 nm (blue), 582 nm (yellow) and 610 nm (red) were synthesized by a sol–gel method. The as-synthesized phosphors were characterized by X-ray powder diffraction (XRD), transmission electron microscopy (TEM), photoluminescence decay lifetimes, photoluminescence excitation and emission spectra. The results showed that photoluminescence intensity varied with excitation wavelength and the doping concentration of Eu3+. The co-doping with Eu3+ compensated the red emission component of the YAG: Dy3+ phosphor. The chromaticity coordinate of YAG: 0.06Dy, 0.09Eu phosphor (0.3263, 0.3334) was very close to that of the ideal white light (0.3333, 0.3333). Thus, the YAG: 0.06Dy, 0.09Eu phosphor can find potential application in simulating the sunlight artificially through fabricating white light emitters.